Penegakan Hukum Terhadap Pelaku Pengrusakan Objek Wisata Ke’te’ Kesu’ Toraja Utara - Salamba, Yogistry Pakita; Riza, Marwati; Aspan, Zulkifli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
This study aims to analyze the enforcement of sanctions against perpetrators of the destruction of tourist objects in Ke'te' Kesu' North Toraja. This research uses empirical legal research methods with a statutory approach. The results of this study indicate that the enforcement of sanctions against the perpetrators of the destruction of tourist objects in Ke'te' Kesu' North Toraja is still less effective and the case has not been followed up, despite having a Regional Regulation of North Toraja Regency Number 7 of 2016. There are several obstacles faced in the application of sanctions in law enforcement against perpetrators of destruction of tourist objects due to, among others: (1) the civil service police unit can’t apply criminal sanctions because it does not have an agreement from the Police, Prosecutor's Office, and the Court; (2) the budget is slow or even non-existent so that the civil service police unit can’t move in guarding every tourist who enters North Toraja, and (3) the lack of personnel of the civil service police unit, so that it does not reach every violation of the destruction of Ke'te Kesu' Toraja Utara tourist objects.